2014
DOI: 10.1080/10508619.2014.916588
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Outcomes of Experiences Deemed Religious: A Longitudinal Investigation

Abstract: Experiences deemed religious (EDRs) are events that a person regards as religious and/or supernatural. This study considered four such experiences-miraculous healing, glossolalia, unusual joy and peace during meditation or prayer, and prayer answered. We proposed a process model and conducted a longitudinal study to address three main research questions: (a) Who are more likely to have EDRs? (b) What effects would the experiences have on the person's subsequent spiritual and psychological conditions? (c) Are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Evoked feelings during religious practice have pronounced effects on social behavior, health, and religious commitment. Feelings of peace and joy during prayer have been associated with increased future religious commitment and improved sleep quality, while other religious experiences such as glossolalia, perception of having prayers answered, and perception of miraculous healing showed no similar effect in a longitudinal analysis ( Hui et al, 2015 ). Frequent spiritual or religious experience has also been associated with enhanced quality of life and positive psychosocial outcomes ( Underwood & Teresi, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evoked feelings during religious practice have pronounced effects on social behavior, health, and religious commitment. Feelings of peace and joy during prayer have been associated with increased future religious commitment and improved sleep quality, while other religious experiences such as glossolalia, perception of having prayers answered, and perception of miraculous healing showed no similar effect in a longitudinal analysis ( Hui et al, 2015 ). Frequent spiritual or religious experience has also been associated with enhanced quality of life and positive psychosocial outcomes ( Underwood & Teresi, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study was part of a large, multiwave, longitudinal online survey. Details of data collection procedure in that research program can be found in Hui, Ng, Mok, Lau, and Cheung (2011) and Hui et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…These studies seek to understand how contemplation can change the practitioner’s attitudes and behavior, most specifically their attention, emotional regulation, and reduction in stress (Britton et al, 2014; Lindahl et al, 2017). Longitudinal studies have used inventories to measure any such changes over a period of time and also addressed the question of what kinds of people are pre-disposed to being changed by meditative practices (Hui et al, 2015). Some have addressed the problems of definitions and descriptions of kinds of contemplative practices, and methodological issues such as a lack of validation with some measures (Van Dam et al, 2018).…”
Section: The Spiritual Exercises and Previous Researchmentioning
confidence: 99%